Navigating complex challenges: digital competence and personal knowledge management in university education to foster skills for lifelong learning. (1st January 2013) - Cinque, Maria; Bortoluzzi, Maria
Web applications and resources offer unique opportunities for lifelong learning and, at university level, to customise the learning environment for individual learners. But the processes of online learning and online knowledge management involve issues of complexity and sustainability that students – even at university level – are not always able to recognise and cope with. This work presents two research case studies, concerning activities carried out within two university courses. The aim of the research was to determine whether specific activities can enhance the development of skills for lifelong learning, such as the ability to search the Internet and use online resources to promote continuous education and learning to learn. Quantitative and qualitative data were gathered within a framework of personal knowledge management and the resulting guidelines are potentially useful both for teachers and learners.